2008
DOI: 10.1371/journal.pone.0002957
|View full text |Cite
|
Sign up to set email alerts
|

Management of Extensively Drug-Resistant Tuberculosis in Peru: Cure Is Possible

Abstract: Aim To describe the incidence of extensive drug-resistant tuberculosis (XDR-TB) reported in the Peruvian National multidrug-resistant tuberculosis (MDR-TB) registry over a period of more than ten years and present the treatment outcomes for a cohort of these patients. Methods From the Peruvian MDR-TB registry we extracted all entries that were approved for second-line anti-TB treatment between January 1997 and June of 2007 and that had Drug Susceptibility Test (DST) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 8 publications
0
40
1
4
Order By: Relevance
“…XDR‐TB is more expensive and difficult to treat than MDR‐TB, and outcomes much worse with higher rates of treatment failure and death . These patients also presented longer duration until culture conversion, a median of 26 months or, accordingly to other series, a median of 183 days until conversion .…”
Section: Objectivesmentioning
confidence: 82%
See 2 more Smart Citations
“…XDR‐TB is more expensive and difficult to treat than MDR‐TB, and outcomes much worse with higher rates of treatment failure and death . These patients also presented longer duration until culture conversion, a median of 26 months or, accordingly to other series, a median of 183 days until conversion .…”
Section: Objectivesmentioning
confidence: 82%
“…However, in many studies, no HIV‐positive patients were found . In one study, the population was specifically HIV‐negative .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients with MDR-TB are treated following the recommendations of the WHO according to defined parameters (World Health Organization, 2010a). There are no official specific recommendations for the treatment of patients with XDR-TB, although positive experiences have been reported (Bonilla et al, 2008). Patients with XDR-TB have fewer options for treatment and risk higher mortalities, especially in HIV-coinfected persons, as has been reported earlier (Gandhi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports address the treatment of XDR‐TB in nonoutbreak settings and where HIV infection is not a comorbidity 40–47 . The results are quite variable, no doubt due to the differences in severity of illness, rapidity of diagnosis, access to second‐line drugs, local expertise in TB treatment, adherence to therapy, sample size, issues related to referral bias, and, perhaps most importantly, the extent of drug resistance.…”
Section: Treatment Outcomesmentioning
confidence: 99%